Spatial range, social structure and behaviour of ‘resident’ short-beaked common dolphins (Delphinus delphis) in the Port Phillip embayment: considerations for their future management and conservation - Mason, Suzanne Jane (Curtin University, 2016)
This study investigated a small community of around 30 short-beaked common dolphins (Delphinus delphis) that show atypical residency to shallow, urbanised Port Phillip Bay, south-eastern Australia. Social structure analyses revealed non-random associations among 12 resident adults, mainly reproductively active females. The community’s seasonal occurrence and behaviour along the embayment’s south-east coast was strongly associated with conditions amenable to prey availably. This atypical habitat preference exposes them to anthropogenic activities not typically considered for common dolphins.